العناصر الداخلية في رواية زينب لمحمد حسين هيكل - Khairul Fuadi (AL MA'ANY, 2024)
The novel "Zaynab" by Muhammad Husein Haikal is one of the first novels in modern Arabic literature. The novel makes Zaynab the main character in the story, the author is very skilled at playing with the reader's emotions through the storyline he builds. To further research, the researcher uses library research methods and qualitative analysis in this study, this study discusses the author's biography, synopsis, and various intrinsic elements in the novel such as ideas, plot, language style, characters, and messages. The results of the study show that this novel criticizes patriarchal traditions, especially forced marriage, and highlights the importance of individual freedom and gender equality. This novel uses a descriptive, simple, and realistic language style to describe rural life in Egypt and the deep emotions of its characters. The message of this novel is the need for fair social change and empathy for disadvantaged individuals. This study contributes to understanding the transformation of Arabic literature from classical to modern through Haikal's work. تعتبر رواية "زينب" للكاتب محمد حسين هيكل من أوائل الروايات في الأدب العربي الحديث. الرواية تجعل زينب الشخصية الرئيسية في القصة، فالكاتب ماهر جدًا في التلاعب بمشاعر القارئ من خلال القصة التي يبنيها. لمزيد من البحث، استخدم الباحث أسلوب البحث المكتبي والتحليل النوعي في هذا البحث، ويناقش هذا البحث سيرة المؤلف وملخصه والعناصر الداخلية المختلفة في الرواية مثل الأفكار والحبكة وأسلوب اللغة والشخصيات والرسائل. وتظهر نتائج البحث أن هذه الرواية تنتقد التقاليد الأبوية، وخاصة الزواج القسري، وتسلط الضوء على أهمية الحرية الفردية والمساواة بين الجنسين. تستخدم هذه الرواية أسلوبًا لغويًا وصفيًا بسيطًا وواقعيًا لوصف الحياة الريفية في مصر والمشاعر العميقة لشخصياتها. رسالة هذه الرواية هي الحاجة إلى التغيير الاجتماعي العادل والتعاطف مع الأفراد الأقل حظا. يساهم هذا البحث في فهم تحول الأدب العربي من الكلاسيكي إلى الحديث من خلال أعمال هيكل